2018
DOI: 10.1111/jfpe.12691
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modeling and thermodynamic properties of rice parboiling

Abstract: Due to the importance of hydration stage for parboiling, related studies are insufficiently addressed in the literature. The objective of this study was to model the moisture absorption kinetics of paddy rice, as well as estimate the thermodynamic properties involved in the hydration. The observed mass transfer in the process was directly influenced by the temperature of the system, showing changes in absorption capacity over time. The models addressed allowed satisfactorily describing the moisture gain under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 36 publications
6
22
0
Order By: Relevance
“…Also, there is the energy used to transport water inside oats, which can be associated to the Gibbs free energy (energy needed to perform work). The positive values of Gibbs free energy showed that the maceration of oats is not a spontaneous process, but is influenced by temperature, corroborating with the results obtained in process of hydration of soybean (Borges et al, ) and rice (Balbinoti et al, ).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Also, there is the energy used to transport water inside oats, which can be associated to the Gibbs free energy (energy needed to perform work). The positive values of Gibbs free energy showed that the maceration of oats is not a spontaneous process, but is influenced by temperature, corroborating with the results obtained in process of hydration of soybean (Borges et al, ) and rice (Balbinoti et al, ).…”
Section: Resultssupporting
confidence: 87%
“…The activation energy (E a ) represents the energy required to occur the diffusive mass transfer process during the hydration process. The E a (10-35 C; Table 3) for oat hydration was 17.88 kJÁmol −1 , lower than that found for wheat (Mattioda et al, 2018) and rice (Balbinoti, Jorge, & Jorge, 2018a). However, it was an expected result since some cereals may present different sizes and composition.…”
Section: Thermodynamic Properties Of the Hydration Processmentioning
confidence: 59%
See 1 more Smart Citation
“…And the study of the thermodynamic properties made it possible to understand the different forms of energies and phenomena involved in this process. 6 Therefore, in this context, the change tendencies of the moisture content and the hardness of the rice kernels, and shear viscosity of rice porridge during the cooking process at different temperature are investigated. In addition, the exponential models or sigmoidal models are tted to experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…The hydration behavior of grains have been studied and their kinetics mathematically described in several studies to predict the moisture uptake of different grains at different temperatures, such as rice (Balbinoti, Jorge, & Jorge, 2018); sorghum (Kashiri, Daraei Garmakhany, & Dehghani, 2012); wheat (Kashaninejad, Dehghani, & Kashiri, 2009); adzuki beans (Oliveira et al, 2013), among others (Miano, Sabadoti, Pereira, & Augusto, 2017). The hydration studies, however, were mostly conducted at isothermal conditions.…”
mentioning
confidence: 99%